The Outcome of Spontaneous Vaginal Delivery Immediately After Previous Cesarean Sections - Karima Abidalla,; Meesa Ahmed,; Taweda Khalifa, (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Women undergoing cesarean section have a higher morbidity and mortality rate than those having vaginal birth. Overall, morbidity and mortality rates secondary to the Trial of Labor After Cesarean (TOLAC) are less than those of repeated cesarean sections. It has long been accepted that TOLAC is a safe and acceptable option for women with previous cesarean section. This study was aimed to investigate the delivery outcome for women who candidate to a trial of spontaneous vaginal delivery immediately after previous cesarean delivery. Methods. A retrospective study was carried out in EL-Beida medical center. This study was from first January to thirtieth June in 2020, including a total of 100 patients with previous cesarean section and that were candidates for attempted vaginal birth. Results. Vaginal birth after cesarean section rate among women with previous cesarean section was 68%. Remaining had repeated cesarean delivery (32%). There was a positive correlation between the age, parity, Bishop score, fetal weight and the mode of delivery, P value (0.056, 0.216, 0.241, 0.151, respectively). Conclusions. The current results fond that age, Bishop score, birth weight, previous vaginal birth, should be considered as factors related to the success of VBAC. Our results are important for women who are pregnant or are planning to become pregnant after a previous CS.